2002
DOI: 10.1034/j.1601-0825.8.s2.3.x
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of HIV in the dental clinic and elsewhere

Abstract: This review focuses on the risk of transmission of HIV in dental practice in developed and developing countries; and as a result of oral sex, perinatal transmission and breast feeding. Postexposure prophylaxis (PEP) and practical measures to control cross-infection with TB are also discussed. There are few data from resource-poor countries where prevalence of HIV and risk of infection are higher--issues that deserve priority. Available information indicates that the risk of HIV transmission in the dental offic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 107 publications
0
26
0
3
Order By: Relevance
“…The risk of transmission of HIV in the dental care setting has been reported to be low [10,11]; however, this does not indicate a zero risk as dentists can be accidentally exposed to the virus and other bloodborne pathogens in the course of treating patients.…”
Section: Discussionmentioning
confidence: 98%
“…The risk of transmission of HIV in the dental care setting has been reported to be low [10,11]; however, this does not indicate a zero risk as dentists can be accidentally exposed to the virus and other bloodborne pathogens in the course of treating patients.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast to the present study, Kadeh et al (6) and Al-Sandook et al (13) reported that most dentists in their studies refused to treat this kind of patient. Current guidelines are that dentists must not refuse to treat a patient solely on the grounds of HIV infection, and they cannot legally refer these patients to speciality clinics for routine dental care (11).…”
Section: Discussionmentioning
confidence: 99%
“…These findings were comparatively low when compared with the findings reported by Sadeghi and Hakimi (4); Aggarwal and Panat (7). Since 1988, WHO has affirmed that all dental professionals must treat HIV patients (11). Dentists are ethically obligated to provide care for patients with infectious disease (12).…”
Section: Discussionmentioning
confidence: 99%
“…Estima-se que após um acidente percutâneo, o risco de soroconversão seja de 0,3%, e após uma exposição mucocutânea a sangue contaminado, o risco é de 0,09% (MCCARTHY ET AL., 2002). Também não existem casos de transmissão do vírus HIV por aerossóis, resultantes da atividade clínica odontológica (MARQUES, 2006).…”
Section: Discussionunclassified